Mesh Partitioning for Efficient Use of Distributed Systems - Chen, Jian; Taylor, Valerie E. (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction Major Issues Related to Mesh Partitioning for Distributed Systems Description of Part Parallel Simulated Annealing Experiments Previous Work Conclusion and Future Work References